2017
DOI: 10.1089/thy.2016.0547
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Papillary Thyroid Carcinoma in Korea with a High Prevalence ofBRAFV600EMutation

Abstract: Genetic alterations in PTC vary among its different histologic variants and seem to be different in each ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 48 publications
4
65
2
1
Order By: Relevance
“…Interestingly, BRAF V600E mutations have rarely been reported in NIFTP cases . In contrast, many other studies, including the original article by Nikiforov et al outlining the nomenclature change to NIFTP, have not shown BRAF V600E mutations in their reported NIFTP cases .…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, BRAF V600E mutations have rarely been reported in NIFTP cases . In contrast, many other studies, including the original article by Nikiforov et al outlining the nomenclature change to NIFTP, have not shown BRAF V600E mutations in their reported NIFTP cases .…”
Section: Discussionmentioning
confidence: 96%
“…NIFTP is a morphological phenotype consistent with RAS ‐like tumor, and cases with BRAF and/or TERT promoter mutation must be excluded, as per the current concept . BRAF V600E mutation was reported in “NIFTP” that fulfilled the morphological criteria by several research groups . These results show that the current nuclear score systems (either three‐point or eight‐point) are not able to differentiate noninvasive follicular patterned thyroid tumors with BRAF V600E mutation and/or lymph node metastasis from NIFTP.…”
Section: Discussionmentioning
confidence: 81%
“…However, this study was based on a single high power still image per case, which probably could not reproduce the whole complexity of lesion encountered in practical settings. In addition, several recent institutional reports from the USA and Korea described NIFTP cases with BRAF V600E and TERT promoter mutations characteristic for conventional PTC . These controversial findings prompted ramifications of NIFTP diagnostic criteria released in 2018 .…”
mentioning
confidence: 99%
“…In spite of Asian continent being a major contributor to worldwide prevalence of thyroid cancer (according to GLOBOCON database; estimated 48% new cases in 2012), the prevalence of NIFTP in Asians has not been reported extensively as compared with the western world . There are limited studies from Asia and even fewer form India and those present have reported a significantly lower prevalence (0%‐5%) as compared to western data (15%‐25%) …”
Section: Introductionmentioning
confidence: 77%
“…The extent of all the changes related to the NIFTP reclassification apparently depends on the incidence of NIFTP in a certain population. Approximately, 30 studies have been conducted in America, Europe and Asia reporting variable incidence . Bychkov et al, in a meta‐analysis, documented an average worldwide prevalence rate of 9.1%, with a lower rate in Asian studies (1.6%) as compared with non‐Asian countries (13.3%) .…”
Section: Discussionmentioning
confidence: 99%